The Role Of Intellectual Capital On Company Value With Profitability As A Mediating Variable: Empirical Study Of LQ-45 Companies On The IDX For The 2020-2022 Period - Taupik Firdaus; Nuryaman Nuryaman (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This research aims to analyze the influence of Transfer Pricing and Capital Intensity on Tax Avoidance in manufacturing sector multinational companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2023 period. The research uses quantitative methods with secondary data obtained from the company's annual financial reports. The research population includes 172 companies, and the sample was selected using a purposive sampling method, resulting in 15 companies with a total of 75 observations. Data analysis was carried out using panel data regression using the Fixed Effect model via Eviews software. The research results show that Transfer Pricing does not have a significant effect on Tax Avoidance because most transactions are domestic. On the other hand, Capital Intensity has a significant effect on Tax Avoidance, indicating that companies with high fixed assets utilize depreciation to reduce tax liabilities. Simultaneously, both variables have a significant influence on Tax Avoidance.